Financial Distress, Free Cash Flow, Employee Diff, and Earnings Management - Sri Maryati; Diah Fitriani; Yusnaini Yusnaini (Jurnal Akuntansi Bisnis, 2023)
This study examines the effects of financial distress, free cash flow and employee diff on earnings management. Companies that experience financial difficulties and have little free cash flow are predicted to carry out earnings management to hide poor financial performance. Companies that experience an increase in the number of workers which is not followed by an increase in profits are also predicted to carry out earnings management. To test the hypothesis, samples were taken from transportation, infrastructure, hotel, restaurant and tourism sector companies listed on the Indonesia Stock Exchange in 2019-2022. A total of 137 observations were available to test the hypothesis. Testing was carried out using regression analysis with the help of Eviews 12. The results showed that free cash flow has positive effect on earnings management but financial distress and employee diff had no effect on earnings management. The practical implication of the research results is that investors must pay attention to cash flow conditions before using profits as a basis for making investment decisions.